Design of beam optics for a Super Tau-Charm Factory. (2nd July 2021) - Lan, J.Q.; Luo, Q.; Zhang, C.; Gao, W.W.; Xu, Y.; Bai, Y.
Abstract: Beam optics design for a Super Tau-Charm Factory (STCF) that planning in China is presented in this paper. This STCF is an electron-positron circular collider characterized with high luminosity, wide energy ranges as well as high longitudinally polarized electron beam. In order to achieve high luminosity, the recently proposed collision scheme based on large Piwinski angle and crab waist sextupole will be adopted. In this paper, the beam optical parameters and their design basis for the STCF storage ring lattice are given. In addition, the preliminary dynamic aperture and beam-beam simulation are studied to get a luminosity more than 0.5 × 10 35 cm -2 s -1 at the optimized energy 2 GeV.